Global assessment of relationships between climate and tree growth. (3rd April 2020) - Wilmking, Martin; van der Maaten‐Theunissen, Marieke; van der Maaten, Ernst; Scharnweber, Tobias; Buras, Allan; Biermann, Christine; Gurskaya, Marina; Hallinger, Martin; Lange, Jelena; Shetti, Rohan; Smiljanic, Marko; Trouillier, Mario
Abstract: Tree‐ring records provide global high‐resolution information on tree‐species responses to global change, forest carbon and water dynamics, and past climate variability and extremes. The underlying assumption is a stationary (time‐stable), quasi‐linear relationship between tree growth and environment, which however conflicts with basic ecological and evolutionary theory. Indeed, our global assessment of the relevant tree‐ring literature demonstrates non‐stationarity in the majority of tested cases, not limited to specific proxies, environmental parameters, regions or species. Non‐stationarity likely represents the general nature of the relationship between tree‐growth proxies and environment. Studies assuming stationarity however score two times more citations influencing other fields of science and the science–policy interface. To reconcile ecological reality with the application of tree‐ring proxies for climate or environmental estimates, we provide a clarification of the stationarity concept, propose a simple confidence framework for the re‐evaluation of existing studies and recommend the use of a new statistical tool to detect non‐stationarity in tree‐ring proxies. Our contribution is meant to stimulate and facilitate discussion in light of our results to help increase confidence in tree‐ring‐based climate and environmental estimates for science, the public and policymakers. Abstract : Tree‐ring records provide global high‐resolution information on tree‐species responses to global change, forest carbon and water dynamics, and past climate variability and extremes. The underlying assumption is a stationary (time‐stable), quasi‐linear relationship between tree growth and environment. Our results show that this assumption might be too simplistic. Non‐stationarity between tree growth and climatic or environmental drivers is evident at global scale.